2022
DOI: 10.1128/jb.00102-22
|View full text |Cite
|
Sign up to set email alerts
|

The Atypical Antipsychotic Quetiapine Promotes Multiple Antibiotic Resistance in Escherichia coli

Abstract: AAP medication is a cornerstone in the treatment of serious psychiatric disease. The AAPs are known to exhibit antimicrobial activity; therefore, a potential unintended risk of long-term AAP use may be the emergence of AMR, although such risk has received little attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Interestingly, while our previous in vitro study demonstrated clinical resistance to ampicillin, ceftriaxone, and a 16-fold increase in MICs to levo oxacin following six weeks of exposure to quetiapine at gutrelevant concentrations (10mg/L (Isolates A-C) or 100 mg/L(Isolates D-F)) 12 , the E.coli isolates cultured from the mouse stool showed no such statistically signi cant increase in susceptibility (Supplemental Fig. 3).…”
Section: Mobile Genetic Elements (Mges) Linked To Quetiapine Exposurementioning
confidence: 79%
See 2 more Smart Citations
“…Interestingly, while our previous in vitro study demonstrated clinical resistance to ampicillin, ceftriaxone, and a 16-fold increase in MICs to levo oxacin following six weeks of exposure to quetiapine at gutrelevant concentrations (10mg/L (Isolates A-C) or 100 mg/L(Isolates D-F)) 12 , the E.coli isolates cultured from the mouse stool showed no such statistically signi cant increase in susceptibility (Supplemental Fig. 3).…”
Section: Mobile Genetic Elements (Mges) Linked To Quetiapine Exposurementioning
confidence: 79%
“…Transitioning from these clinical observations to a more controlled experimental setting, we sought to emulate the potential impact of quetiapine on the gut microbiota. In our previous investigations, we found that E. coli developed MDR after six weeks of in vitro exposure to quetiapine, even at concentrations that were four-fold lower than those estimated in the human colon, and whole-genome sequencing analysis of quetiapine-exposed isolates revealed mutations in known AMR genes 12 . Based on these ndings, we hypothesized that chronic exposure of bacteria to SGAs such as quetiapine over time can indirectly select for AMR mechanisms in the gut microbial community of patients who often necessitate years of quetiapine treatment.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A key underexplored question that arises from these reciprocal drug–microbiome interactions is how they impact one another given the ability of microorganisms to evolve and change over short time scales within the host ( Zhao et al, 2019 ; Lieberman, 2022 ; Garud et al, 2019 ; Snitkin et al, 2013 ; Gatt and Margalit, 2021 ). Specifically, given that bacteria rapidly evolve resistance to antimicrobial drugs, it is plausible that adaptation to host-targeting drugs that are also antimicrobial will alter bacterial drug metabolism or its transport ( Rosener et al, 2020 ; Kyono et al, 2022 ). Such adaptions have been repeatedly observed with standard antibiotics ( Alekshun and Levy, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…A key underexplored question that arises from these reciprocal drugmicrobiome interactions is how they impact one another given the ability of microorganisms to evolve and change over short time scales within the host [12][13][14][15][16] . Specifically, given that bacteria often rapidly evolve resistance to antimicrobial drugs, it is plausible that adaptation to hosttargeting drugs that are also antimicrobial will alter bacterial drug metabolism or its transport 17,18 . Such adaptions have been repeatedly observed with standard antibiotics 19 .…”
Section: Introductionmentioning
confidence: 99%